Faktor yang Mempengaruhi Sikap Pengguna Terhadap Produk Halal di Malaysia - Azzamurni Bt Mohtar; Siti Muyassarah Binti Abd Nasir (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study purpose to examine the factors influencing consumer attitudes towards the branding of halal products, with a focus on knowledge about halal products, health as a priority, and the role of the halal logo in influencing consumer attitudes towards purchasing Ayam Bismi. A mixed-method approach is used in this study, involving a combination of quantitative and qualitative methods. Document analysis of surveys and observations is employed to obtain the study's findings. Overall, the study found that the halal logo has a significant positive relationship with consumer attitudes towards the intention to purchase halal products, especially Ayam Bismi. The halal logo is identified as a crucial factor in influencing consumer attitudes towards halal products, helping to reduce doubts about the halal status of the product. The study's findings indicate a positive relationship among all examined factors, providing evidence that the presence of the halal logo has a positive influence on consumer attitudes and purchase intentions